Transient global amnesia - Marazzi, Chiara; Scoditti, Umberto; Ticinesi, Andrea; Nouvenne, Antonio; Pigna, Federica; Guida, Loredana; Morelli, Ilaria; Borghi, Loris; Meschi, Tiziana (Acta Biomedica Atenei Parmensis, 2014)
Transient Global Amnesia (TGA) is a clinical syndrome characterized by temporary inability to form new memories described as anterograde amnesia. It is associated with retrograde amnesia and repetitive questioning. During the attack patients remain conscious and communicative and personal identity is preserved. Focal neurological symptoms and epileptic features are absent and general conditions appear intact. The ability to store new memories gradually recovers and subjects return to normal conditions except for a substantial amnestic gap for the duration of the attack. TGA has an incidence of 3-8 per 100 000 people per year. It usually affects patients between the ages of 50 and 70 years, at an average age of 61 years; occurrence in patients younger than 40 years of age is rare. The rate of recurrence is between 6% and 10% per years. No gender prevalence has been recorded. The patients with definite TGA have a very good prognosis; their rate of subsequent major vascular events is less than 1% per year.